2017
DOI: 10.1021/acs.cgd.7b00136
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization Diagram for Antisolvent Crystallization of Lactose: Using Design of Experiments To Investigate Continuous Mixing-Induced Supersaturation

Abstract: This study investigates the effects of key process parameters of continuous mixing-induced supersaturation on the antisolvent crystallization of lactose using D-optimal Design of Experiments (DoE). Aqueous solutions of lactose were mixed isothermally with antisolvents using a concentric capillary mixer. Process parameters investigated were the choice of antisolvent (acetone or isopropanol), concentration of lactose solution, total mass flow rate, and the ratio of mass flow rates of lactose solution and antisol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 50 publications
2
37
0
Order By: Relevance
“…Because of the high supersaturation degree generated in antisolvent adding period and the limited micromixing in the conventional stirred tank crystallizer, developing a method for the effective control of the antisolvent mass transfer process is still a key concern . The most common approach to antisolvent addition is a batch droplet or capillary‐based mixing . The limited interfacial mass transfer area used for the droplet approach and the undesired mixing result in a wide particle‐size distribution and an irregular crystal morphology, which are the fatal drawbacks for pharmaceutical and other chemical manufacture.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the high supersaturation degree generated in antisolvent adding period and the limited micromixing in the conventional stirred tank crystallizer, developing a method for the effective control of the antisolvent mass transfer process is still a key concern . The most common approach to antisolvent addition is a batch droplet or capillary‐based mixing . The limited interfacial mass transfer area used for the droplet approach and the undesired mixing result in a wide particle‐size distribution and an irregular crystal morphology, which are the fatal drawbacks for pharmaceutical and other chemical manufacture.…”
Section: Introductionmentioning
confidence: 99%
“…Many attempts have been made to devise a quick nucleation method in order to obtain the desired lactose crystal size. Previous studies have demonstrated that seeding, use of anti-solvent, agitation, sonocrystallisation and combined high power ultrasound (US) and carbonation (Kougoulos et al, 2010;Parimaladevi and Srinivasan, 2014;Patel and Murthy, 2009;Zeng et al, 2000;Zamanipoor and Mancera, 2014;Zisu et al, 2014;Dincer and Zisu, 2016;MacFhionnghaile et al, 2017;Xun et al, 2017) can modify nucleation kinetics, thereby lactose crystal size, shape and yield are enhanced.…”
Section: Accepted Manuscript 1 Introductionmentioning
confidence: 99%
“…Ibuprofen has an aromatic ring, a methyl, and a carboxyl functional group in its structure, whilst α-lactose monohydrate has two pyranose rings and a water molecule, forming a dimer in its structure. An αlactose monohydrate is built from a moiety of β-Dgalactose and α-D-galactose, joined by a 1,4 glycosidic bond between C1 of galactose and C4' of the glucose unit [29,[31][32][33]. Fig.…”
Section: Crystal Structurementioning
confidence: 99%